Clostridium difficile: A rare cause of pyogenic liver abscess - DULUNDU, ENDER; ÜLGER, NURVER; YEGEN, ŞEVKET CUMHUR (ELSEVIER SCI LTD, 2016)
Extra-intestinal infections due to Clostridium difficile have been reported rarely. Herein we report a case of pyogenic liver abscess from toxigenic C. difficile in an 80-year-old non-hospitalized woman with diabetes mellitus, cerebrovascular and cardiovascular diseases. The patient was admitted to the emergency department with fever and abdominal pain. There was no history of diarrhea or use of antibiotics. Laboratory parameters revealed signs of inflammation and elevated AST and ALT levels. Abdominal ultrasound and computer tomography showed multiple focal lesions in the bilateral liver lobes and hydropic gallbladder with stones. The patient underwent cholecystectomy and the liver abscesses were drained. Toxigenic C difficile strains were isolated from the drained pus and also from the stool sample. According to repetitive-element PCR (rep-PCR) analyses both organisms were the same. The organisms were susceptible to antibiotics. Despite proper antibiotic therapy and surgical drainage, the patient succumbed to her illness. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Anaerobe; Clostridium difficile; Pyogenic liver abscess; INFECTIONS